Rapid and Sensitive Detection of Salmonella Typhimurium on Plastic Food Processing Plates by Using Wireless Biosensors. (10th December 2015) - Liu, Yuzhe; Horikawa, Shin; Du, Songtao; Chai, Yating; Hu, Jiajia; Wang, Fengen; Chin, Bryan A
Abstract : Food products can be contaminated with bacteria, spores, and other pathogens at any point in the farm-to-table continuum. This paper presents an investigation into rapid, sensitive detection of Salmonella Typhimurium on plastic food processing plates by using wireless magnetoelastic (ME) biosensors. In this research, a planar spiral coil was microfabricated and employed as a surface-scanning detector for real-time, in-situ measurement of the biosensors without sample preparation and/or enrichment in the testing process. The ME biosensor consists of an ME resonator, made from metallic glass (Metglas alloy 2826MB), as the signal transducer and E2 phage as the bio-molecular recognition element that is engineered to selectively bind with Salmonella Typhimurium . Both measurement sensors (multiple E2 phage-coated biosensors) and control sensors (multiple biosensors without phage) were prepared and distributed on a food grade plastic plate contaminated with Salmonella Typhimurium with known volumes and concentrations. The resonant frequency changes of the measurement sensors due to specific binding of Salmonella Typhimurium were found to be statistically different from those of the control sensors.